Education, retirement and career transitions for 'Black' ex-professional footballers : 'from being idolised to stacking shelves' - Campbell, Paul (Emerald points., 2020)
Drawing on a combination of interviews and auto-ethnographic data, Education, Retirement and Career Transitions for 'Black' Ex-Professional Footballers provides a case-study of 16 'black' British male professional footballers' preparedness and experiences of retirement and transition from careers as professional athletes to mainstream work. The author examines these men's sporting experiences during three life phases: As professional schoolboy footballers; as professionals; and during retirement and career transition to mainstream careers. In doing so, this book expands on how these men's experiences of and preparedness for retirement and career transition are influenced and often complicated by the cultures, practices, and expectations that shaped the professional game when they were players. It also offers an account of the ways these experiences were complicated by issues of race. Researchers, students, sports enthusiasts and anyone interested in questions of race, masculinity, employment, retirement, mental health, and professional sport in late modern Britain will find Education, Retirement and Career Transitions for 'Black' Ex-Professional Footballers useful, informative and engaging.